Gender dan Pembangunan: Peran DPPPA dalam Penanganan Kekerasan Pada Perempuan di Provinsi Aceh - Utami, Adella; Nurwati, Nunung; Bustami, Reevany; Wibowo, Hery (Jurnal Community, 2024)
This research examines the role of the DPPPA (Department of Women's Empowerment and Child Protection) in gender-based development in Aceh Province, particularly in addressing violence against women. The novelty of this study lies in the DPPPA's involvement in managing cases of violence against women as part of gender-based development efforts, an area that has not been extensively researched previously. The research employs a qualitative case study methodology, utilizing case study techniques. Data collection is conducted through interviews and literature reviews. The findings indicate that the protection provided by the DPPPA through the UPTD PPA (Technical Implementation Unit for the Protection of Women and Children) for women victims of violence includes counseling to help victims overcome trauma, emotional support, and guidance on steps to obtain protection by directing victims to appropriate health services, shelters, and rehabilitation programs. The objective is to ensure that victims receive adequate support and protection while fostering socio-cultural changes that can prevent future violence and promote gender-based development in Aceh.